Keanekaragaman Tumbuhan dan Preferensi Pakan Monyet Ekor Panjang di Kawasan Telaga Warna Bogor : Diversity of Plants Used as Food by Long-Tailed Monkeys in the Telaga Warna Area of Bogor - Hartati, Bunga Resa; Marpaung, Sutan Sahala Muda; Setiarno, Setiarno; Trianingtyas, Andhira; Samad, Radhiatunnisa S; Putra, Rizky Auliansyah; Putro, Dhymas Sulistyono (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Telaga Warna Bogor is a conservation area consisting of a Nature Reserve (CA) and Telaga Warna Nature Park (TWA) which harbors potential flora and fauna. The Long-tailed Macaque is one of the protected animals in the area and, with the rise of its IUCN conservation status, has been included in the red list of endangered species. The purpose of this study was to determine the food preferences of Long-tailed Macaques in the Telaga Warna area. The method used to determine food preferences was the line transect method, while the potential food trees were identified using the grid method, supplemented by a literature study for additional data on food preferences. The data analysis used was descriptive and qualitative. The food plant data was analyzed to determine density, frequency, dominance, and INP. The results of the study showed that the INP analysis of Villebrunea rubescens (42.21), Slonea sigun (33.82), and Castanopsis Argentea (22.91) had the highest values of the 17 food trees, indicating that these three plant species are quite abundant and have high potential as food for long-tailed macaques. The parts of plants most frequently eaten by long-tailed macaques were the fruit (47%), followed by the flowers (29%), and the leaves (24%). KEYWORDS Plant diversity, food preferences, long-tailed macaques, Telaga Warna Bogor.